Associations of the oral microbiota and Candida with taste, smell, appetite and undernutrition in older adults - Kristina S. Fluitman (Nature Portfolio, 2021)
Abstract Poor taste and smell function are widely thought to contribute to the development of poor appetite and undernutrition in older adults. It has been hypothesized that the oral microbiota play a role as well, but evidence is scarce. In a cross-sectional cohort of 356 older adults, we performed taste and smell tests, collected anthropometric measurements and tongue swabs for analysis of microbial composition (16S rRNA sequencing) and Candida albicans abundance (qPCR). Older age, edentation, poor smell and poor appetite were associated with lower alpha diversity and explained a significant amount of beta diversity. Moreover, a lower Streptococcus salivarius abundance was associated with poor smell identification score, whereas high C. albicans abundance seemed to be associated with poor smell discrimination score. In our population, neither the tongue microbiota, nor C. albicans were associated with poor taste or directly with undernutrition. Our findings do suggest a host-microbe interaction with regard to smell perception and appetite.